The call for spiritual formation in Protestant theological institutions in South Africa - M. Naidoo (Acta Theologica)
Spiritual formation is a significant component of the educational work of a theological institution that prepares students for church leadership. Theological institutions have a responsibility to engage students in reflecting on the spiritual life, to provide opportunities for students, to deepen their spiritual journeys and to develop in students a spiritual maturity that is required of future church leaders. This article argues the need for Protestant theological institutions in South Africa to be more deliberate in developing students spiritually within the challenges of their South African context.